White privilege and clinical social work practice: Reflections and recommendations - Davis, Ashley; Gentlewarrior, Sabrina (Journal of Progressive Human Services, 2015)
This exploratory study examined how seasoned White social workers grappled with the presence and effects of White privilege on their clinical practice. Data were collected in focus groups; findings were surfaced through thematic analysis. Five themes emerged: the role of engaging in continuous self-awareness in clinical practice; the complexity of using intersectionality to inform our work; the necessity of addressing White privilege in clinical conversations; the importance of creating strategies for use of power; and the process of engaging in life-long growth. These workers demonstrated awareness of, and accountability for, White privilege. Implications for progressive social work practice are discussed.
Keywords: OFDIG; antiracisme; approches et analyses; blanchité; intersectionnalité; pratique clinique; privilèges; racisme; ressource en ligne; systèmes d'oppressions; thématiques; travail